Peran UKM dalam Perekonomian: Studi Kasus Kota Yogyakarta - Jaka Sriyana (Unisia, 2006)
The article below traces and investigates the real sector of economy case study at Yogyakarta. The real sector of economy has an important role in term of Indonesian economy especially in preparing vocation. These real sectors ofeconomy need regu lating by govemment to increase them, in paticular in overcoming their obstacles. The regulation should include all field of real sectors, for instance bank access, economical situation. Thus, the goal of this is to support dan increase their competitive advantages and to sustain their business.